Ecoarchaeological and Archaeozoological Aspects of Prehistoric Settlement Viničica near Josipdol - Olujić, Boris (Array, 2007)
Viničica is stony hill which dominates at wide area of Ogulin valley, situated nearby Josipdol (Central Croatia). It is actually a complex of two uphill, Velika (elevation 450) and Mala Viničica (elevation 350, 7) with relating plateaus and declines. This dual hillfort was continually settled during Bronze and Iron Age. Underneath Viničica there was a Roman settlement of probably municipal status. There are numerous findings of epigraphs, walls and the graves dating from 1-4 century AC. From the middle of 19th century objects found at hillfort and local area are being transferred to Archaeological museum Zagreb. Since 2002. systematic research of settlement complex is going on. Researches include intensive field survey, making of digitalized geodetic base, air photographing and excavating certain parts of the settlement (objects for living, stone walls, approaching roads, etc.). Special attention in this research is taking place in ecological aspect of everyday life of those prehistoric inhabitants. Most researches assume that this settlement can be identifying with Iapod capital Metulum, which was mentioned by C. Iulius Octavianus in his memoirs (antic authors Appian and Cassius Dio later communicate about it). Also, a numerous animal remains were found in this settlement. Analysis and interpretations of those osteological animal materials can provide a lot of information about nutrition, everyday way of life during various eras of this community.